Economic Planning: Time for Reconsideration? - Kafouros, Wassily (Economic Journal of Development Issues, 2010)
In non-capitalist countries economic planning has remained a fundamental tool of achieving different goals. However the collapse of the Union of Soviet Socialist Republic (USSR) in the 1990s along with other the dissolution of the WARSA Pact have given rise room to questions on the necessity of economic planning. This has created the illusion that capitalism or free market mechanism is the superior or at least the only realistic way to handle every socio-economic aspect of this world. However the blame for the collapse of the various socialist systems should not fall on the systemic deficiencies of economic planning but on the political institutions responsible for its application1. Planning is only an instrument and one cannot accuse an instrument for being misused. Unless we understand exactly where and why the various People's Republics failed to deliver what they had promised, it will be virtually impossible to inquire into the theoretical deficiencies, or lack thereof, of economic planning. Key words: Economic Planning; Collapse of USSR; Condemn; Political institutions; Instrument; Failure Economic Journal of Development Issues Vol. 9 and 10 (2008 & 2009) Combined Issue Page: 167-177